Evaluasi Kinerja BNNP Sumatera Utara dalam Pemberantasan Narkotika di Kelurahan Belawan Bahagia - Panjaitan, William Alfredo; Sinaga, Rudi Salam; Simamora, Beltahmamero (Mahesa Research Center, 2025)
Narcotics abuse in Indonesia is a serious problem that threatens the younger generation and social stability. North Sumatra is one of the provinces with the highest rate of narcotics abuse, with Belawan Bahagia Village as one of the vulnerable areas. This study aims to evaluate the performance of the North Sumatra Provincial National Narcotics Agency (BNNP) in efforts to eradicate narcotics in the region. The method used was qualitative descriptive with in-depth interview techniques with five key informants, including BNNP officers, police members, community leaders, and local residents. Data analysis was conducted using six policy evaluation indicators according to William N. Dunn: effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy. The results of the study show that although BNNP has experienced institutional strengthening, challenges in resource distribution, limited program reach, and low community participation are still the main obstacles. On the other hand, there are positive efforts through the involvement of local communities and cooperation with law enforcement officials. This study recommends collaborative strategies and improved community-based approaches to increase policy effectiveness in drug-prone areas such as Belawan Bahagia.